The Basic Orientations of Contemporary’ Crime Policy (Kriminalističke teme, 2004)
The author elaborates issues related to Contemporary Crime Policy- Politics of Crime Control-Politics of Crime, from the two point of view. First one is relate to the linguistic problems of define terms into Bosnian Language and second part which is relate, to short explane of the main element of contemporary Crime Policy : Crime Prevention.